Development of a water-mist cooling system: A 12,500 Kcal/h air-cooled chiller - Chung-Neng Huang; Ying-Han Ye (Energy Reports, 2015)
Global warming and energy exhaustion problems are becoming a severe problems, of which energy conservation and carbon reduction are the most critical. Between 40% and 48% of the total electricity used in a building is consumed by air conditioning systems. The development of a supersonic water-misting cooling system with a fuzzy control system is proposed to optimize existing condenser noise, space, and energy consumption, as well as to address problems with cooling capacity resulting from improper control between compressors and condensers. An experimental platform was established for conducting tests, observing cooling efficiencies, and calculating power saving statuses. Comparing the observed cooling efficiency, a temperature difference of 5.4~êC was determined before and after the application; this is significant regarding efficiency. The method produces no pollution or water accumulation. When compared with fixed frequency air-cooled water chillers, an exceptional energy saving of 25% was observed. The newly developed supersonic mist-cooled chiller is an excellent solution to increasing water and electricity fees.
Keywords: 330; Dual-effect fuzzy control; Supersonic oscillator; Water-mist cooling